A Highly Sensitive Graphene Aerogel Pressure Sensor Inspired by Fluffy Spider Leg. Issue 15 (14th July 2021) - Tian, Ye; Han, Jingkai; Yang, Jiankui; Wu, Huaping; Bai, Hao
Abstract: Pressure sensors serve as an important part in electronic skin, flexible and wearable devices, by converting external stimuli into easily identifiable electronic signals, where sensitivity is one of the most critical factors for the performance. Here, a highly sensitive pressure sensor is established based on a graphene aerogel film (GAF) with biomimetic architecture inspired by the fluffy leg of spiders to comprehend the gentle vibration of spider web. The biomimetic GAF with lamellar layers and interlayer dendrites is prepared by bidirectional freezing technique. The special fluff‐like dendritic structure between layers accounts for the GAF sensor with excellent performance under pressure: a high sensitivity of 7.48 kPa –1, a low detection limit of 5 Pa, ultrafast response time as 31 ms, and recovery time of 38 ms with working stability after more than 1000 cycles. This biomimetic GAF pressure sensor paves the path for flexible electronics as demonstrated by monitoring real‐time human pulse and weighing of ultralight objects. Additionally, the approach highlights an efficient route of developing highly sensitive pressure sensors through mimicking various biological architectures. Abstract : A biomimetic graphene aerogel pressure sensor with hierarchical architecture mimicking the fluffy spider leg is developed by bidirectional freezing technique. The assembled sensor has a high sensitivity of 7.48 kPa –1, establishing potential applications in flexible and wearable electronic devices for monitoring real‐time human pulse and weighing of ultralight objects.